THE BIBLICAL VIEW OF DIOGENES' CYNICISM PHILOSOPHY IN CHRISTIANITY - Harold Siregar; Bartolomeus Diaz Nainggolan (Diegesis : Jurnal Teologi, 2024)
This study aims to find out whether the Bible supports those who are cynical, especially the cynicism of Diogenes. This type of research is useful to examine a topic that has not been studied in depth before or to broaden one's understanding of a topic that has been studied before using various perspectives. This research collects and studies all literature and sources related to the Philosophy of Cynicism, especially Christian spiritual literature sources such as the Bible. Lack of faith, or "unbelief", is one of the symptoms of cynicism. The Bible always warns its readers not to put full trust in man. According to Proverbs 3:5, "Trust in the LORD with all your heart and lean not on your own understanding." Paul also commands Christians not to follow the pattern of this world. They would live their lives as they pleased and would ignore the advice of pastors and leaders. However, in the church, defying God's authority is considered apostasy.